MELIA Results 2024: evaluation of AICCRA interventions in Senegal on access to and use of climate-smart agriculture (CSA) and climate information services (CIS) - Thiaw, Moussa; Diouf, Abdoul Mouhamed; Said, Shakira Hachim; Josiane, Kengne; Prosper, Houessionon; Edorh, Theopile; Worou, Omonlola Nadine; Wane, Abdrahmane (International Livestock Research Institute, 2024)
This MELIA study evaluates the impact of AICCRA interventions on farmers' access to and use of Climate-Smart Agriculture (CSA) and Climate Information Services (CIS) in Senegal. Based on a sample survey of 427 farming households across six regions, the study employs quantitative methods to estimate use rates and assess dissemination pathways. Results indicate that 59.38% of beneficiaries have used CIS and/or CSA, with confidence intervals suggesting a total adoption range between 83,421 and 97,072 individuals. The most widely accessed CIS include short-term rainfall forecasts (69.14%) and seasonal forecasts (47.66%), yet critical information on post-harvest handling and climate finance remains largely unavailable.